Self-Employed – Still an Entrepreneur or an Employee? About the Dilemmas of the Conflict of Economic Freedom and Employee Protection - Koczur, Sebastian; Piwowarska, Kinga; Świątkowski, Andrzej Marian (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
Self-employed is not and cannot become a worker. The same reservation applies to an employee who has decided or been forced to run a self-employed sole trader. For this reason, according to the authors, the idea of crossing the border between economic and labour law in the current legal state cannot be implemented.